Preparation of cetyl palmitate-based PEGylated solid lipid nanoparticles by microfluidic technique. (February 2021) - Arduino, Ilaria; Liu, Zehua; Rahikkala, Antti; Figueiredo, Patrícia; Correia, Alexandra; Cutrignelli, Annalisa; Denora, Nunzio; Santos, Hélder A.
Abstract: In recent years, several studies have shown that the use of solid lipid nanoparticles (SLN) as a colloidal drug delivery system was more advantageous than lipid emulsions, liposomes and polymeric nanoparticles. SLNs have numerous advantages of different nanosystems and rule out many of their drawbacks. Despite the numerous advantages of SLNs, translation from the preclinical formulation to the industrial scale-up is limited. In order to provide a reproducible and reliable method of producing nanoparticles, and thus, obtain an industrial scale-up, several methods of synthesis of nanoparticles by microfluidic have been developed. Microfluidic technique allows a good control and a continuous online synthesis of nanosystems compared to synthesis in bulk, leading to a narrow size distribution, high batch-to-batch reproducibility, as well as to the industrial scale-up feasibility. This work described the optimization process to produce SLNs by microfluidics. The SLNs produced by microfluidics were characterized by complementary optical and morphological techniques and compared with those produced by bulk method. SLNs were loaded with paclitaxel and sorafenib, used as model drugs. The anti-cancer efficiency of the SLNs formulation was estimated with 2D and 3D tumour models of two different cell lines, and the cellular uptake was also studied with fluorescence-assisted measurements. Graphical abstract: Image, graphical abstract